IDENTIFYING THE WORKING CONDITIONS OF FLAT DIE PELLET PRESS HOLES WITH PREDETERMINED GEOMETRICAL PARAMETERS - Kurka, Roman; Maksymiv, Volodymyr; Gumnitskyy , Yaroslav (Forestry, Forest, Paper and Woodworking Industry, 2012)
The method for determining the working capacity of flat die pellet press holes with predetermined geometrical parameters has been proposed.